Determinants of Residents’ Word-of-Mouth Behaviour and Support for Tourism - Blasco López, Maria Francisca (2020)
This research explores residents’ support for tourism by introducing—for the first time—the variable of residents’ word-of-mouth intention. The tested model proposes that residents’ support for tourism is influenced by residents’ word-of-mouth and tourism benefits; the model also examines the impacts of community attachment and community involvement on the benefits of tourism. The relationship between tourism benefits and residents’ word-of-mouth is the most significant indication of the tested model, followed by the linkage between tourism benefits and support for tourism. Besides this, the positive and significant effect of residents’ word-of-mouth on their support for tourism has been proven. The results stress the need for increased focus on the benefits of tourism by increasing community attachment, as they reveal that more attached residents lead to more positive perceptions of the benefits of tourism, consequently having a higher effect on their word-of-mouth intention and support for tourism.